Escritura creativa para el fortalecimiento de competencias comunicacionales, en sexto grado, Escuela Matilde Hidalgo de Procel, periodo 2024-2025 - Pardo Gualán, Alisson Mishelle (2025)
Creative writing has proven to be a useful tool in developing students' communication skills, as it promotes innovation in ideas and allows the connection of academic content with personal experiences. This provides students with the confidence to express themselves, strengthens their identity, and fosters the development of critical and reflective skills, facilitating learning that is connected to their reality. The main objective of this research is to analyze the use of creative writing for the development of communication skills in sixth-grade students at the “Matilde Hidalgo de Procel” Basic Education School during the 2024-2025 school year. Additionally, three specific objectives were established: first, to diagnose the communication skills that students have acquired during their learning process; second, to determine institutional experiences with creative writing to improve communication skills; and third, to establish a didactic proposal through creative writing to strengthen students' communication skills. The research approach was mixed, exploratory-descriptive, with a non-experimental design. The sample consisted of one teacher and twenty sixth-grade students from class “B,” totaling twenty-one human talents. The results indicated a lack of involvement in creative writing activities, which limits students' opportunities to perform well in the classroom and when communicating. Therefore, it was considered necessary to propose a didactic workshop on creative writing aimed at reinforcing the communication skills, as it allows students to explore different writing formats and styles, contributing to the development of confidence and security, skills that are often limited by educational methods that prioritize memorization or mechanical learning